Technological Innovation and Growth of SMEs In Bangalore: Does Innovation Facilitate Growth of Firm Size? - Subrahmanya, M H Bala (The Asian Journal of Technology Management (AJTM), 2011)
This paper probes the drivers, dimensions, achievements and outcomes of technological innovations carried out by SMEs in the auto-components, electronics and machine tool sectors of Bangalore in India. Thereafter, it probes the relationship between innovation and growth of SMEs by (i) estimating correlation between innovation sales and sales growth; (ii) calculating innovation sales for high, medium and low growth innovative SMEs and doing one way ANOVA, and (iii) ascertaining the influence of innovation sales, along with investment growth and employment growth on sales growth by means of multiple regression analysis. The paper brings out substantial evidence to argue that innovations of SMEs contributed to their growth. Â  Key words: SMEs, technological innovations, sles growth, bangalore, india